Leachate treatment-chitosan as an adsorbent for heavy metal ions - Norfahana, Rashid (2009)
Leachate contains several of heavy metals which become potential pollution for water resources (ground and surface) and the soils. Chitosan reported to be an effective adsorbent to remove heavy metals in leachate. The main objective of this study is to evaluate the effectiveness of heavy metal ions removal from leachate using chitosan. Iron (II) solution was used for synthetic sample analysis to determine the optimum operating condition of the sample in the function of pH, contact time, agitation speed and chitosan dosage. The result indicated that the optimum conditions for chitosan to be the most effective to adsorb metal ions is at pH sample 9, agitation speed 50 rpm, contact time 20 min and the dosage of chitosan 30 mg/L. For actual leachate sample analysis, the highest percentage of metal removal obtained at 50 mg/L of chitosan dosage. The adsorption percentage for Iron ions is 36.8 % while the adsorption percentage for Managanese ions is 28.6. A treatment system for leachate is proposed in this study. The design of treatment system that consists of pH stabilization tank, metal adsorption tank and sedimentation tank is based on the optimum operating condition. The tanks are design to treat 1m v 3 of leachate at a time with chitosan dosage provided is 300g/m